Qatar : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper discusses measures required to enhance nonhydrocarbon revenue to support fiscal consolidation in Qatar. Qatar depends heavily on the hydrocarbon sector for exports and revenue receipts. The authorities have embarked on fiscal consolidation, underpinned by cuts to current expenditures and enhanced efforts to raise additional revenue. Safeguarding Qatar's wealth to ensure intergenerational equity and ensure adequate resources for the implementation of the second National Development Strategy would entail increased mobilization of nonhydrocarbon revenue in the near to medium term. Exploring other sources of tax revenue to diversify the government revenue structure and build a stable tax revenue base is also critical.